2010
DOI: 10.1021/nn101781v
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Monolayer Graphene Oxide

Abstract: Mechanical properties of ultrathin membranes consisting of one layer, two overlapped layers, and three overlapped layers of graphene oxide platelets were investigated by atomic force microscopy (AFM) imaging in contact mode. In order to evaluate both the elastic modulus and prestress of thin membranes, the AFM measurement was combined with the finite element method (FEM) in a new approach for evaluating the mechanics of ultrathin membranes. Monolayer graphene oxide was found to have a lower effective Young's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
651
5
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,067 publications
(702 citation statements)
references
References 60 publications
41
651
5
5
Order By: Relevance
“…35 In that case, the size of the AFM tip was 23.9 nm, which is larger than our AuNPs. In this regard, the pressure applied on GO is even greater in our system.…”
mentioning
confidence: 64%
“…35 In that case, the size of the AFM tip was 23.9 nm, which is larger than our AuNPs. In this regard, the pressure applied on GO is even greater in our system.…”
mentioning
confidence: 64%
“…3 The plentiful amount of oxygen-containing functional groups on GO sheets provide easy modification of GO for various applications. 4,5 Biopolymer surface-functionalized GO nanosheets were reported to be biocompatible and non-toxic at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, important to note that this class of materials is likely to intrinsically consist of multi--layers although single--layer structures have been synthesized. It has been shown that for 2D materials, such as graphene 37 and graphene oxide, 38 there exists a linear relationship between the elastic moduli and the number of layers. Accordingly, an enhanced mechanical strength of a multi--layered structure is anticipated.…”
mentioning
confidence: 99%